2016
DOI: 10.1080/15459624.2016.1161199
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of estimated core body temperature measured with the BioHarness and rectal temperature under several heat stress conditions

Abstract: Monitoring and measuring core body temperature is important to prevent or minimize physiological strain and cognitive dysfunction for workers such as first responders (e.g., firefighters) and military personnel. The purpose of this study is to compare estimated core body temperature (Tco-est), determined by heart rate (HR) data from a wearable chest strap physiology monitor, to standard rectal thermometry (Tre) under different conditions.  Tco-est and Tre measurements were obtained in thermoneutral and heat st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
2
17
0
1
Order By: Relevance
“…One would expect from passive heating that the algorithm would underestimate the rise in T c , since there is no heat-generating information contained in the heart rate. The unexpected underestimation for passive heating was reported by Seo et al (75) in their validation of the algorithm implemented in a commercial PSM device. Seo et al also found that the algorithm had acceptable performance for both treadmill and cycle exercise.…”
Section: Parsimonious Models Derived From Computational Physiologymentioning
confidence: 68%
“…One would expect from passive heating that the algorithm would underestimate the rise in T c , since there is no heat-generating information contained in the heart rate. The unexpected underestimation for passive heating was reported by Seo et al (75) in their validation of the algorithm implemented in a commercial PSM device. Seo et al also found that the algorithm had acceptable performance for both treadmill and cycle exercise.…”
Section: Parsimonious Models Derived From Computational Physiologymentioning
confidence: 68%
“…Further studies among military populations have confirmed similar levels of agreement [RMSD 0.21 °C; systematic bias (0.02 ± 0.11) °C; 95% LoA ±0.48 °C] when conducting work wearing chemical and biological (CB) protective clothing [27], when wearing combat uniforms during jungle operations (− 0.01 °C; 95% LoA ±0.58 °C) [28], and during road marching (0.02 °C; 95% LoA ±0.76 °C) [23]. Slightly wider systematic bias has been observed during treadmill exercise wearing athletic clothing [(0.3 ± 0.4) °C; 95% LoA ± 0.7 °C) or CB protective clothing [(− 0.1 ± 0.4) °C; 95% LoA ±0.7 °C] [29]. These studies have shown that ECTemp, while not a replacement for direct measurement techniques, provides a noninvasive indication of deep body temperature that could easily be implemented in a range of athletic and occupational situations, such as technicians wearing EOD protective clothing.…”
Section: Introductionmentioning
confidence: 99%
“…And yet, high numbers of deaths occur among agricultural workers annually that are attributed to HRI. From current research on core body temperature and the effects of hydration, clothing, work-rate and environmental conditions (Courville, Wadsworth, and Schenker 2016;Hoyt et al 2017;Schenker 2013;Seo et al 2016), it is clear that simply training workers to drink more water or rest in the shade will not necessarily decrease occurrence of HRI. Between the years 1992 and 2013, at least 689 workers in the United States died from HRI, and 56,114 were injured severely enough to result in days away from work (Centers for Disease Control and Prevention 2008;U.S.…”
Section: Introductionmentioning
confidence: 99%